Celebrating Polyoxometalate Chemistry - Pope, Michael T.; Sadakane, Masahiro; Kortz, Ulrich (European journal of inorganic chemistry, 2019)
Michael Pope, Masahiro Sadakane, and Ulrich Kortz present a short history of polyoxometalates, listing important anniversaries.